Emergence of repurposed drugs as modulators of MCU channel for clinical therapeutics. (November 2021) - Vishnu, Neelanjan; Wilson, Justin; Madesh, Muniswamy
Highlights: The highly selective mitochondrial Ca 2+ uptake channel MCU play a crucial role in cellular Ca 2+ homeostasis and bioenergetics. Recently, De Mario et al., conducted small molecule screen to identify MCU modulators that control mitochondrial Ca 2+ uptake as a proof-of-concept. Graphical abstract: Image, graphical abstract